Advanced in developmental organic and inorganic nanomaterial: a review - Khalid, K. (Taylor and Francis Inc., 2020)
With the unique properties suchÂ as high surface area to volume ratio, stability, inertness, ease of functionalization, as well as novel optical, electrical, and magnetic behaviors, nanomaterials have a wide range of applications in various fields with the common types including nanotubes, dendrimers, quantum dots, and fullerenes. With the aim of providing useful insights to help future development of efficient and commercially viable technology for large-scale production, this review focused on the science and applications of inorganic and organic nanomaterials, emphasizing on their synthesis, processing, characterization, and applications on different fields. The applications of nanomaterials on imaging, cell and gene delivery, biosensor, cancer treatment, therapy, and others were discussed in depth. Last but not least, the future prospects and challenges in nanoscience and nanotechnology were also explored. Â© 2020, Â© 2020 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.